Penegakan Hukum Terhadap Pelaku Penipuan Investasi Online Studi kasus di Kepolisian Daerah (POLDA) Nusa Tenggara Timur - Frengky Adolfo Lay; Debi F.Ng. Fallo; Orpa Ganefo Manuain (Badan Penerbit STIEPARI Press, 2025)
Online business does make it easier for fraudsters to carry out their actions. Although online investment fraud has been partially revealed, many of the actions taken by individuals against these actions have not yet reached the legal realm. The research method used by the author is empirical legal research, the research data collection technique uses systematic interviews and is based on the research object, data analysis in this study is qualitative descriptive analysis. The results of the study show that criminal law enforcement against perpetrators of gold investment fraud is carried out in accordance with criminal law regulations, namely the Criminal Code (KUHP) Article 378, the police as investigators have difficulty finding the perpetrators so they decide to stop the investigation in accordance with Article 109 of the Criminal Procedure Code. The gold investment fraud case that occurred in East Nusa Tenggara in 2019 showed that law enforcement by the police was hampered by law enforcement factors, facilities and infrastructure factors, community factors and cultural factors.